ÜSTÜN YETENEKLİ ÖĞRENCİLERİN ÖĞRENME STİLLERİ İLE PROBLEM ÇÖZME BECERİLERİ ÜZERİNE BİR ÇALIŞMA. - KONTAŞ, Hakkı; TOPAL, Tuncay (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2015)
The purpose of this research is to investigate the relationship between gifted students' learning styles and their problem solving skills. The relational screening model was used in the study. The sample of the study was consisted of 106 gifted students attending sixth, seventh and eighth grades at Ordu Science and Art Center (SAC) during 2011-2012 academic year. The data was collected using personal information form, Learning Styles Inventory developed by Kolb and Problem Solving Inventory developed by Heppner and Peterson. In this research, the data were analyzed using frequency, t-test, chi-squared and kruskal-wallis test. The results showed that the learning styles of gifted students did not differ significantly in terms of gender variables but did in terms of grade level. It was seen that problem solving skills did not differ significantly in terms of grade level and learning styles but problem solving skills were significantly different in terms of gender.